Here and There - Smith, Tamara Ellis; Daviddi, Evelyn (Cambridge, MA Barefoot Books, 2019)
After Ivan's parents separate, he has trouble finding joy at either of their homes until he discovers that the birds and music that he loves may be found in both places.
Keywords: Divorce -- Juvenile fiction; Birdsongs -- Juvenile fiction; Songs -- Juvenile fiction; Divorce -- Fiction; Birdsongs -- Fiction; Songs -- Fiction